LEGALITY AND ILLEGALITY OF NO WORK NO PAY POLICY ON ACADEMIC STAFF UNION OF UNIVERSITIES (A CASE STUDY OF FEDERAL UNIVERSITY OF TECHNOLOGY, OWERRI 2019-2023) (NAU Journal of Technology and Vocational Education, 2026)
This study examined the legality and implications of the “no work, no pay” policy on members of the Academic Staff Union of Universities (ASUU) at the Federal University of Technology, Owerri from 2019 to 2023. Three research questions and two hypotheses guided the study. The study’s design adopted a descriptive survey design. The population consisted of 956 ASUU members, from which a sample of 282 respondents was selected using the Taro Yamane formula and simple random sampling technique. Data were collected through a validated questionnaire, with a reliability coefficient of 0.88 obtained through the use of Cronbach Alpha. Frequency tables and percentages were used to answer research questions, while chi-square statistics tested the hypotheses at a probability of 0.05. Findings revealed that the policy has legal implications for employment contracts, infringes on staff rights, disrupts academic activities, and negatively affects students’ interests. It was also found to contradict provisions of the Nigerian Labour Act. The study recommends policy review and clearer implementation guidelines.
Keywords: legality; illegality; no work; no pay; Academic staff union of universities